Criminal Accountability of Children as Perpetrators of the Crime of Obscenity - Baryadi Baryadi; Jawade Hafidz (Jurnal Hukum Khaira Ummah, 2021)
This study aims to determine and analyze the concept of criminal responsibility against children who are perpetrators of criminal acts of sexual abuse, study the decision of the case number 03/Pid.Sus.Anak/2020/PN.Wsb. The legal research method used in this study is a sociological juridical approach. Criminal responsibility for perpetrators of sexual abuse is not only applied to adults but also to children, as regulatedArticle 76E of the Law on Child Protection, and the sanctions are regulated in Article 82 of Law No. RI. 17 of 2016 concerning Child Protection. The application of sanctions against children who have committed crimes has been regulated in Article 71 and Article 82 The Juvenile Criminal Justice System Act includes principal crimes and actions. Children who commit crimes of sexual abuseIn the decision of Case Number: 03/Pid.Sus-Anak/2020/PN.Wsb the judge has given criminal sanctions to the child perpetrator with two main criminal sanctions, namely imprisonment (article 71 paragraph 1 letter e) and job training sanctions in lieu of fines. if not paid (article 71 paragraph 1 letter c), Law Number 11 of 2012 concerning the juvenile criminal justice system. In The imposition of criminal penalties for children who are perpetrators of crimes must be wiser by taking into account the best interests of the child, and imprisonment is only carried out as a last resort. negative for the future.